Proposal of a Framework for Innovation Competencies Development and Assessment (FINCODA) - Juan A. Marin-Garcia; Mª Angeles Andreu Andres; Lorena Atares-Huerta; Lourdes E Aznar-Mas; Amparo Garcia-Carbonell; Fernando González-Ladrón-de-Guevara; Begoña Montero Fleta; M.Jose Perez-Peñalver; Frances Watts (WPOM : Working Papers on Operations Management)
In this article we propose a model of innovation competence of people, based on the existing literature to integrate and complement the existing models. The main contribution of this work consists in demonstrating the differences and similarities of current models and in providing a conceptual definition for each model element. In this way, both researchers and people in charge of Human Resources in companies can obtain a framework to design measuring instruments to assess the innovation competence, which can fulfil the twofold demand requirement of validity and reliability.